Peripheral Blood MicroRNA Levels in Females with Cocaine Use Disorder - Viola, Thiago Wendt (J Psychiatr Res, 2019)
BACKGROUND: There is growing emphasis in the field of psychiatry on the need to identify candidate biomarkers to aid in diagnosis and clinical management of addictive disorders. MicroRNAs (miRNAs) are small nucleotide sequences with the ability to regulate gene expression at the transcriptomic level. However, the role of miRNAs as potential biomarkers for addiction is still underexplored. Based on translational and clinical findings, we compared the expression levels of microRNA-124 (miR-124), microRNA-181 (miR-181), and microRNA-212 (miR-212) between a group of females with cocaine use disorder (CUD; n = 30) and a group of healthy female controls (HC; n = 20). METHODS: Blood expression levels of miR-124, miR-181, and miR-212 in the HC and CUD group were determined by qPCR, using two miRNAs as endogenous controls (miR-24 and miR-126). Substance use behavior was assessed by self-report using the Addiction Severity Index (ASI-6) and depressive symptoms severity was measured using the Beck Depressive Inventory (BDI-II). Urine screen test was performed to detect cocaine metabolites. RESULTS: Mir-124 and miR-181 were upregulated in the CUD group (p > 0.01). Furthermore, increased cognitive/affective depression symptoms were identified among a CUD subgroup with the higher miR-181 expression levels (p > 0.05). No significant difference in expression levels was found for miR-212. CONCLUSIONS: MiR-124 and miR-181 show promise as biomarkers for CUD when assessed in the peripheral blood. Further investigation is needed to elucidate the molecular mechanisms underlying these associations and to validate target genes regulated by these miRNAs.